Effects of sodium hyaluronate and methylprednisolone alone or in combination in preventing epidural fibrosis. (1st October 2013) - Shaban, Madhat; Aras, Yavuz; Aydoseli, Aydin; Akcakaya, Mehmet Osman; Sencer, Altay; Bayindir, Cicek; Izgi, Nail
<x xml:space="preserve">Abstract</x> Objective: Epidural fibrosis and leptomeningeal adhesion formation are common causes of failed back surgery syndrome (FBSS). We employed a rat model of lumbar laminectomy to evaluate the histopathological effects of sodium hyaluronate (HA) and methylprednisolone (MP) alone or in combination on post-laminectomy epidural fibrosis. Methods: Thirty-two male Sprague-Dawley rats were divided into four groups. All rats underwent three-level lumbar laminectomy. In the treatment groups, HA solution, MP, or a combination of both was applied locally to the epidural spaces of the laminectomy fields. No neurological deficits or pathological wound site changes were observed in any of the groups. At the end of the sixth week, all rats were sacrificed, and the laminectomy vertebral column areas were removed en-bloc. Specimens were evaluated by an expert neuropathologist according to histopathological criteria. Results: The results of the three treatment groups were separately compared with the control group to assess epidural fibrosis. Minimal reduction in the rate of epidural fibrosis was observed in the groups treated with HA or MP compared with the control group. However, no significant difference in epidural fibrosis was noted between the combined treatment group and the control group. Conclusions: Our study showed that MP and HA, given separately, significantly reduce post-laminectomy epidural fibrosis; however, the combination of these drugs is not effective. Further investigation is needed to address the causative drug interactions.